دور العلاقات العامة في المجال الرياضي من وجهة نظر العاملين فيها - إبراهيم قاسم; ناصر رهام (Latakia University Journal -Medical Sciences Series, 2017)
تشكل العلاقات العامة خلية مهمة من جسم أي مؤسسة لما لها من دور هام وفعال في تحقيق الأهداف ، وفي المجال الرياضي تزداد الأهمية بسبب جماهيرية هذا القطاع . ولذلك جاءت هذه الدراسة التي تسعى إلى التعرف على دور وأهمية العلاقات العامة في المؤسسات الرياضية في الجمهورية العربية السورية من وجهة نظر العاملين لكي تعطي صورة عن واقع عمل هذا التشكيل في الهيكل التنظيمي ولهذا الغرض اتخذ المنهج الوصفي بأسلوب المسح التحليلي وطبق على عينة مكونة من 44 فرداً يمثلون نسبة 88% من مجتمع الأصل ليتوصل إلى جملة من النتائج كان أهمها أن هناك اختلاف في وجهة نظر العاملين حول دور وأهمية العلاقات العامة حسب محاورها وأنه لا توجد درجات متدنية لمدى فهم واستخدام العلاقات العامة من قبل العاملين فيها . institution because of its important and active role in achieving its goals. The importance of the public relation is increasing in the sports field because of the mass of this sector. Thus this study seeks to identify the role and importance of public relations in sports institutions in the Syrian Arab Republic, from the perspective of workers in order to illustrate of the reality of the functioning of this sector in the organizational structure .the descriptive method is used with analytical survey manner . The method was applied to a sample of 44 individuals representing 88% of the research community. Thestudy concluded with several important resultswhich include that there is a difference in the employees’point of view about the role and importance of public relations according to axes of the study. There are no low degrees of how to understand and use by the public relations staff.